2014
DOI: 10.12789/geocanj.2014.41.041
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Cape Breton Island and Newfoundland, Canada: Geophysical Modeling of pre-Carboniferous 'Basement' Rocks in the Cabot Strait Area

Abstract: Magnetic and gravity data from northeastern Cape Breton Island, southwestern Newfoundland, and the intervening Cabot Strait area were compiled and used to generate a series of maps displaying magnetic (filtered total field, first and second derivative) and gravity (Bouguer anomaly onshore, free-air anomaly offshore) information to enhance the anomaly pattern associated with regional geology. With further constraints from previously published seismic reflection interpretations and detailed maps of onshore geolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…It extends to the northeast through the Boisdale Hills where it coincides with a Carboniferous fault system (MacIntosh BrookGeorges River). From there it has been postulated to extend across the Cabot Strait to the south coast of Newfoundland (Barr et al 1998(Barr et al , 2014aRogers et al 2006). To the southwest, the terrane boundary is suggested to be offset at the Strait of Canso by the Canso fault and inferred to follow the western margin of the Creignish Hills (King 2002;Barr et al 2012).…”
Section: Geological Settingmentioning
confidence: 99%
“…It extends to the northeast through the Boisdale Hills where it coincides with a Carboniferous fault system (MacIntosh BrookGeorges River). From there it has been postulated to extend across the Cabot Strait to the south coast of Newfoundland (Barr et al 1998(Barr et al , 2014aRogers et al 2006). To the southwest, the terrane boundary is suggested to be offset at the Strait of Canso by the Canso fault and inferred to follow the western margin of the Creignish Hills (King 2002;Barr et al 2012).…”
Section: Geological Settingmentioning
confidence: 99%
“…1) shifted the tectonostratigraphic terranes dextrally by approximately 200 km (White et al 2003). Recent geophysical interpretations (Barr et al 2014) suggest no similar movement along the Cabot Strait to the north of Cape Breton Island.…”
Section: (3)mentioning
confidence: 99%
“…The subparallel Wilkie Brook and Aspy faults bound a narrow block of basement suggesting a positive flower structure that cuts the Horton, Windsor, and Mabou Groups. A similar configuration is postulated for St. Paul Island [ Barr et al , ].…”
Section: Timing and Amount Of Slipmentioning
confidence: 99%
“…Some authors [e.g., Bradley , ; Hibbard and Waldron , ; Hayward et al , ] have suggested major dextral strike‐slip motion along the Hollow fault, noting its parallel alignment to other Appalachian‐trend faults. Others, noting the large vertical offsets of basement along the fault, and the rapid offshore thickening of the Windsor Group [ Keppie et al , ; Giles , ], have emphasized normal faulting [e.g., McCutcheon and Robinson , ; Dehler and Potter , ; Cook et al , ; Barr et al , ]. Post‐Viséan thrust faults have also been interpreted at depth in St. Georges Bay and west of Cape Breton Island [ Durling and Marillier , ; Durling et al , ; Hayward et al , ], suggesting that shortening may also have played a role in the later history of this boundary.…”
Section: Timing and Amount Of Slipmentioning
confidence: 99%
See 1 more Smart Citation